Asam Lemak Omega-3 Dan Hubungannya DenganPenyakit Kardiovaskular - Ririn Anjelin; Nadia Raihana; Maimum; Fefri Ferianti; Harry Saputra (PHARMANAJA : PHARMACEUTICAL JOURNAL OF UNAJA, 2022)
Cardiovascular diseases are the number one global cause of death, the two most common are coronaryartery disease and stroke. Data suggests that high omega-3 consumption has a benefit in preventingcardiovascular diseases. The report of observations, clinical , animal and in vitro studies havedemonstrated the benefits of omega-3 prevent and treat cardiovascular disease. Although the mechanismis not clear, but it has been shown that the cardiovascularprotection effect of omega-3 fatty acids may becaused by its role influencing biological effects on lipid and lipoprotein metabolism, platelet function,arterial cholesterol distribution, vascular function and inflammatory response.